PERAN DAN STRATEGI RESERVATION SECTION DALAM MENINGKATKAN PENJUALAN KAMAR DI NEW SAPHIR HOTEL YOGYAKARTA - , YUSNIA WIDYANINGSIH; , Arina Pramusita M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
In a hotel the reservation section is needed, with the reservation section will allow guests to book rooms. Reservation at a hotel section has an important role in increasing the sales room reservation section due to the hotel will streamline operations. In this paper carried out research at New Saphir Hotel Yogyakarta on the reservation section. To increase the sales room reservation section in New Saphir Hotel Yogyakarta has a strategy in receiving and processing the reservation. In addition, to address the issues - issues such as cancellation of reservation of room in the handle section will make a designation on the order form with a cancel mark.